A whispering-gallery-mode microlaser based on dual erbium-doped microspheres. (October 2021) - Yan, Jing; Wang, D.N.; Liu, Xin; Chen, Jikai
Highlights: We present a WGM microlaser based on dual erbium-doped microspheres. The dual microsphere microcavity laser has a narrower linewidth than that of a single microsphere microcavity laser and more sensitive to the change of pump source power. It also has the advantages of cost, small size, low threshold and continuous wavelength tunability. The microlaser can greatly reduce the volume of optical integrated devices and reduce the cost of optical components, which promotes the development of large-scale integration with other optical communication elements such as waveguides, optical modulators, and optical fibers. Abstract: We demonstrate a low-cost whispering gallery mode tunable microlaser based on dual erbium-doped microspheres, which is created by directly doping erbium ions when melting the tapered fiber tip by electrode discharge of a fusion splicer. The incident light from the tapered fiber is diverged into the microsphere and stimulates whispering gallery mode. The light field of whispering gallery mode interacts with the internal gain material, erbium ions, and ends up with lasing. The quality factor (Q) value of the device is up to 1.4 × 10 4 . When the pumping laser power changes continuously from 4.6 mW to 7.5 mW, the lasing wavelength shifts from 1560.14 nm to 1560.49 nm, the lasing emission power can be tuned from 0.25 µW to 0.41 µW.